Effect of secondhand smoking, determined by urinary cotinine level on bone health - Ji Hyun Moon; Mi Hee Kong; Hyeon Ju Kim (International Journal of Preventive Medicine, 2018)
Background: We evaluated the relationship between secondhand smoke (SHS) inhalation, as verified by urinary cotinine levels, and bone health. Methods: We analyzed the nationwide, population-based, cross-sectional health survey. We included 1936 men aged 50 years or older who checked bone mineral density (BMD) from the Korean National Health and Nutrition Examination Survey (2008–2010). Current smokers assessed by urinary cotinine levels higher than 500 ng/mL were excluded (n = 616). Exposure to SHS was determined using a 50 ng/mL urinary cotinine threshold. Results: The estimated prevalence of SHS exposure in our cohort was 13.9%. After adjusting for age and body mass index (BMI), T-scores at total femur (P < 0.001), femoral neck (P < 0.001), and lumbar spine (P = 0.004) were lower in SHS exposure versus nonexposure groups. Impaired bone health (osteopenia or osteoporosis) at femoral neck or lumbar spine was evident in 61.7% and 48.6% of SHS exposure and nonexposure cases, respectively (P = 0.004). Moreover, after adjusting for age, BMI, and health habits, the odds ratio for impaired bone health in the SHS exposure group was 1.89 (95% confidence interval: 1.31–2.74). Conclusions: Our findings suggest that SHS exposure, determined by urinary cotinine levels, is negatively associated with BMD and is a leading cause of impaired bone health in Korean men.